Geometric Design for Relocation of National Road Sei Duri-Mempawah Section, West Kalimantan using AutoCAD®2D - Noviantini Nurjannah, Siti; Rifai, Andri Irfan; Akhir, Adinda Fajarika (DAS Institute, 2022)
The International Port of Kijing is a National Strategic Project built as part of the Pontianak Port development. Therefore, it is necessary to design road geometrics to support the port's service level. This research proposes the relocation and geometric layout of the port of Kijing access road. The Sei Duri-Mempawah Section in West Kalimantan is where the data was collected. The design method used is SE PDGJ 2021 and finalized by AutoCAD®2D. The research results obtained design speed (Vr) = 60 km/hour, superelevation (e) = 8%, full circle horizontal curved type with the radius of curve design (R) = 500 m and intersection angle (ꞵ) = 35°, obtained horizontal arch length (Lc) = 305.37 m. Vertical alignment calculations are performed from the STA. 0+000 up to SAT. 1+400, we get a vertical curve (Lv) = 50 m and five vertical curves consisting of 3 crests and two sag curves.